Temperature gradient interaction chromatography of linear polyethylene and isotactic polypropylene. (28th September 2021) - Macko, T.; Arndt, J.-H.; Yu, Youlu; Brüll, R.
Abstract: Samples of linear polyethylene and isotactic polypropylene were separated according to their average molar mass using temperature gradient interaction chromatography (TGIC) with mobile phases at near critical composition. It is known that at the critical mobile phase composition, the adsorption of polymers is very sensitive to variations of the temperature. This effect was utilized here. The temperature of the column (Hypercarb™) was changed from 80 °C to 170 °C according to a programmed temperature gradient. Polymers were first adsorbed in the column at 80 °C and desorbed by the temperature increase. In effect, the polymers eluted at different temperatures. The higher the molar mass, the higher both the elution temperature and the elution volume. This suggests that TGIC has the potential to improve separations of polyolefins according to their molar mass and will allow to separate polyolefins according to their long-chain branching content. Graphical abstract: Image 1 Highlights: PE and PP can be separated according to molar mass at critical conditions. Separation occurs according to molar mass not hydrodynamic volume of polymers. Elution volumes of polymers increase with their weight average molar mass.